Intraparenchymal Hemorrhage in a patient with Post-Traumatic Craniectomy and Severe Thrombocytopenia Due to Fatal Acute Dengue: A Case Report - Puerto-Horta, Sergio Andres; Muñoz-Tovar, Andrea; Charry-Cuellar, José Daniel (Brazilian Journal of Case Reports, 2025)
Intracranial complications in dengue fever are uncommon but have been increasingly reported in severe cases. Dengue fever is a mosquito-borne viral illness caused by the dengue virus, which usually presents mild symptoms such as fever, headache, and myalgia. In a minority of cases, the disease can progress to more severe forms characterized by plasma leakage, severe thrombocytopenia, and bleeding. Although neurological manifestations are not typical in dengue infections, factors such as severe thrombocytopenia and previous neurosurgical interventions may predispose patients to intracranial hemorrhagic events. This case report presents an 18-year-old female with a fatal intraparenchymal hemorrhage, occurring in the context of severe dengue and a history of prior post-traumatic craniectomy. This case illustrates how dengue-related thrombocytopenia and endothelial dysfunction can trigger catastrophic intracranial bleeding in areas of prior structural brain injury. Considering preexisting neurosurgical lesions as potential sites of secondary hemorrhage in dengue patients with severe thrombocytopenia.